MODERNIZATION OF THE NATIONAL SYSTEM OF PREVENTION OF YOUTH OFFENSES IS A REQUIREMENT OF THE PERIOD (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
the thesis covers the theoretical–practical basis for transferring the Prevention of youth offenses from the traditional "reactive" model (punishment after an incident) to the proactive, risk-based and "scientific conclusion—recommendation—result" logic within the framework of resolution PD-1 of January 5, 2026. Social Prevention, which relies on digital transformation and community-family-education, as well as restorative mechanisms, are justified as tools to increase institutional efficiency.